Efikasi Ekstrak Daun Tuba sebagai Anti Rayap Alami (Efficacy of Tuba Leaves Extract as a Natural Antitermite) - Syarif Hidayatullah; Andi A Rizaldy; Helmi Gracia; Syahidah Syahidah (Masyarakat Peneliti Kayu Indonesia, 2017)
Wood preservation is one way to enhance the durability of wood, especially for low grade natural durable woods. The aim of this research was to evaluate the efficacy of tuba (Derris elliptica)leaves extract against the subterranean termite, Coptotermes sp. The leaves was milled and extracted with ethanol solvent to give it’s extracts. There were two kinds of antitermite test which were conducted in this study, namely direct test (stomach toxic test) and indirect test (respiratory toxic test). The mortality of termites and the weight loss of the paper discs were used to determine antitermite activity of the extract. The result showed that the higher concentration of the extract, the higher mortality of termites for both of the test. The concentration of the extract were 2, 4, and 6% with the mortality 40.0, 69.1 and 93.3%, respectively for direct test and 71.5, 75.8 and 89.7%, respectively for indirect test. Moreover, the weight losses of paper discs of direct test were 5.29, 3.07 and 1.94%, respectively.Keywords: Derris elliptica, natural antitermite, preservative, tuba leaves ekstract